Pengaruh Gaya Kepemimpinan Kompensasi Dan Beban Kerja Terhadap Turnover Intention Pada Koperasi Serba Usaha Sentosa - Putri Febrika Ali; Deby R Karundeng; Olfin Ishak (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of leadership style, compensation, and workload on employee turnover intention at Koperasi Serba Usaha "Sentosa". Turnover intention is a critical indicator in maintaining the stability of human resources, particularly in cooperatives that rely on employee loyalty and productivity. The research employs a quantitative approach using survey methods, with questionnaires distributed to 60 respondents who are active employees of the cooperative. Multiple linear regression analysis is used to examine both simultaneous and partial effects of the independent variables on the dependent variable. The results show that leadership style and compensation have a negative and significant effect on turnover intention, while workload has a positive and significant effect. These findings indicate that improvements in leadership style and compensation systems, along with better workload management, can reduce employees' intention to leave the cooperative. The practical implications of this study can serve as a foundation for Koperasi Serba Usaha "Sentosa" in designing more effective employee retention strategies.